The role and changing paradigm of India's assistance to Nepal: Case of the education sector - Tanu M. Goyal (Indian Council for Research on International Economic Relations (ICRIER), 2019)
India is seen as a key developmental partner to Nepal with the latter being one of the first receipts of development aid from India. Development aid from India to Nepal has not only been associated with creation of infrastructure in the country but also with human capital development and ensuring long-term sustainability. Technical assistance and vocation training for skill development have been the focal points of India's development cooperation programme. Development aid has thus been a cornerstone of India-Nepal relation. However, in the recent past, due to the political, administrative and constitutional changes in Nepal, the relation between the two countries has evolved, which has also affected India's development partnership programme with Nepal. In July 2018, the Government of Nepal made changes to the design of India's development partnership programme, which has an impact on India's small development project (SDP) scheme, through which a majority of India's assistance in social sector was facilitated since the year 2003. This paper examines the impact of India's development assistance on the education sector in Nepal and the effectiveness of the SDP scheme in enabling the same. Findings are based on an analysis of secondary information and a primary survey conducted in Nepal using ethnographic principles of research. Two broad categories of inputs were collected - disaggregated data on the quantum of assistance under the SDP scheme and qualitative inputs in terms of perception, experiences and anecdotes on India's development assistance in the education sector. Data was analysed using statistical tools and presented using QGIS. Findings of the study are used to make recommendations on how the design of India's development assistance to Nepal can be renewed.
Keywords: F35; F63; I22; I25; O15; O19; P33; 330; Development Partnership; Foreign Aid; Education Sector; Social Development; Small Development Projects; Sustainable Development; India-Nepal Relations